2017
DOI: 10.1080/02786826.2017.1296103
|View full text |Cite
|
Sign up to set email alerts
|

A practical set of miniaturized instruments for vertical profiling of aerosol physical properties

Abstract: In situ atmospheric aerosol measurements have been performed from a Manta unmanned aircraft system (UAS) using recently developed miniaturized aerosol instruments. Flights were conducted up to an altitude of 3000 m (AMSL) during spring 2015 in Ny-Ålesund, Svalbard, Norway. We use these flights to demonstrate a practical set of miniaturized instruments that can be deployed onboard small UASs and can provide valuable information on ambient aerosol.Measured properties include size-resolved particle number concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…These photometers measure the aerosol-particle light-absorption coefficient (σ abs ) by detecting the change of attenuation of light due to deposited aerosol-particle mass on sample filter. They have been installed on airship platforms (Rosati et al, 2016), tethered balloon platforms (Ran et al, 2016;Ferrero et al, 2014Ferrero et al, , 2016, or unmanned aircraft systems (UASs; Markowicz et al, 2017;Telg et al, 2017;Bärfuss et al, 2018) to address the vertical BC distribution. To investigate human exposure to health-harming BC-containing aerosol particles from combustion sources, they have been used for mobile measurements (Cepeda et al, 2017, and references therein;Alas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These photometers measure the aerosol-particle light-absorption coefficient (σ abs ) by detecting the change of attenuation of light due to deposited aerosol-particle mass on sample filter. They have been installed on airship platforms (Rosati et al, 2016), tethered balloon platforms (Ran et al, 2016;Ferrero et al, 2014Ferrero et al, , 2016, or unmanned aircraft systems (UASs; Markowicz et al, 2017;Telg et al, 2017;Bärfuss et al, 2018) to address the vertical BC distribution. To investigate human exposure to health-harming BC-containing aerosol particles from combustion sources, they have been used for mobile measurements (Cepeda et al, 2017, and references therein;Alas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate human exposure to health-harming BC-containing aerosol particles from combustion sources, they have been used for mobile measurements (Cepeda et al, 2017, and references therein;Alas et al, 2018). Subramanian et al (2007), Vecchi et al (2013), and Lack et al (2008) have shown that liquid-like brown carbon can significantly bias filter-based absorption measurements, since this organic carbon wraps around filter fibers and alters their structural properties. Aerosol samples contain water vapor represented by its relative humidity (RH).…”
Section: Introductionmentioning
confidence: 99%
“…These photometers measure the aerosol particle light absorption coefficient (σabs) by detecting the change of attenuation of light due to deposited aerosol particle mass on sample filter. They have been installed on airship platforms (Rosati et al, 2016), tethered balloon platforms (Ran et al, 2016;Ferrero et al, 2014, Ferrero et al, 2016 or unmanned aircraft systems (UAS;Markowitz et al, 2017, Telg et al, 2017, Bärfuss et al, 2018 to address the 55 vertical BC distribution. To investigate human exposure to health-harming BC-containing aerosol particles from combustion sources, they have been used for mobile measurements (Capeda et al, 2017 and references therein;Alas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, to address vertical profiling of BC with fast rh changes, particle light absorption measurements require a high temporal resolution of about seconds. Telg et al (2017) presented a study using an unmanned aircraft system (UAS) for vertical profiling of aerosol physical 75 properties including the aerosol particle light absorption coefficient measured by an absorption photometer. In their study, a significant decrease of σabs at around 1000 m altitude is visible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation